Civil Engineering And The Science Of Structures - Andrew Solway
Civil engineering is one of the oldest engineering fields. Civil engineers are involved in the design and construction of various structures, including high-rise buildings, sports stadiums, canals, dams, and bridges. This book gives readers a up-close look at the technology used to build various structures around the world, including the ancient pyramids, the Eiffel Tower, the Golden Gate Bridge, and modern skyscrapers. Readers learn about the design process and tools used by civil engineers and are guided through a design challenge to create their own stable structures.